Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12885-016-2820-1
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase activity plays a Key role in the aggressive phenotype of neuroblastoma

Abstract: BackgroundThe successful targeting of neuroblastoma (NB) by associating tumor-initiating cells (TICs) is a major challenge in the development of new therapeutic strategies. The subfamily of aldehyde dehydrogenases 1 (ALDH1) isoenzymes, which comprises ALDH1A1, ALDH1A2, and ALDH1A3, is involved in the synthesis of retinoic acid, and has been identified as functional stem cell markers in diverse cancers. By combining serial neurosphere passages with gene expression profiling, we have previously identified ALDH1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 47 publications
0
31
0
1
Order By: Relevance
“…Additionally, induction of CYP1A1 in presence of diesel exhaust particles were extensively reported in human bronchial cells [58]. Apart from studies related to different types of cancers [59, 60], ALDH1A3 was also previously reported in connection with virus infections like human papilloma virus and respiratory syncytial virus [61-63]. Altogether, these significant differentially expressed genes noted in our study related to different metabolic modifications inside the cell and reasonably linked to virus infections, therefore, we selected these genes for validation in context to RNA virus infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, induction of CYP1A1 in presence of diesel exhaust particles were extensively reported in human bronchial cells [58]. Apart from studies related to different types of cancers [59, 60], ALDH1A3 was also previously reported in connection with virus infections like human papilloma virus and respiratory syncytial virus [61-63]. Altogether, these significant differentially expressed genes noted in our study related to different metabolic modifications inside the cell and reasonably linked to virus infections, therefore, we selected these genes for validation in context to RNA virus infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…shRNA knockdown of ALDH1A2 reduced colony and tumorsphere formation in vitro (Hartomo, et al, 2015). Similarly, inhibition and knockout of isoform ALDH1A3 led to reduction in NB tumor initiating cells (TICs) as demonstrated by reduced colony formation and reduced tumorsphere passaging (Flahaut, et al, 2016). However, despite these in vitro results, when ALDH12A knockdown cell lines were injected subcutaneously into mice, there was no difference in tumor formation and only a slight, non-significant difference in tumor size (Hartomo, et al, 2015).…”
Section: The Search For Neuroblastoma Cscsmentioning
confidence: 99%
“…ALDH1 izoenzimlerinin aktivitesi, CRISPR/ Cas9 teknolojisi kullanılarak hastadan köken alan ksenograft tümörleri kullanan çalışmada, nöroblastom kök hücrelerinin agresif doğasıyla ilişkilendirilmiştir. 96 Hayvan modellerinde, CRISPR/Cas9 teknolojisi kullanan DNMT3a transaktivasyonu, beyin hücrelerinin metilasyonunun düzenlenmesine katkıda bulunmaktadır. 97 CRISPR/Cas9 teknolojisini kullanarak NRAS mutant hücre hattında rehber RNA (gRNA) lar aracılığıyla mutant NRAS geninin susturulması, hücreleri spesifik inhibitörlere karşı daha duyarlı hâle getirmiştir.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified